2018
DOI: 10.14692/jfi.14.4.111
|View full text |Cite
|
Sign up to set email alerts
|

Sebaran Nematoda Sista Kentang di Wonosobo dan Banjarnegara, Jawa Tengah

Abstract: Distribution of Potato Cyst Nematode in Wonosobo and Banjarnegara, Central JavaPotato cyst nematode (PCN), Globodera spp., is the primary pathogens that infect potato plants and has been distributed world wide. This study aimed to determine the geographic distribution and species of PCN that infect potato plants in Wonosobo and Banjarnegara, Central Java through a survey, morphological and molecular approaches. Morphological characters were observed among cyst (fenestra diameter, distance from anus to the fene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…The results of observations found eggs attached to the roots and tubers of potatoes (Syafii et al, 2018;Žibrat et al, 2021). While imago was found on potato stems.…”
Section: Characteristics Of Phthorimaea Operculellamentioning
confidence: 92%
“…The results of observations found eggs attached to the roots and tubers of potatoes (Syafii et al, 2018;Žibrat et al, 2021). While imago was found on potato stems.…”
Section: Characteristics Of Phthorimaea Operculellamentioning
confidence: 92%
“…RKN infestation in potato soil in Sumatera and Java far exceeded this threshold, but the nematode effect on potato yield reduction was not obvious (Hadisoeganda, 2006b). As much as 114 J2/100 g soil or 2-675 cysts/100 g soil of PCN were reported (Hadisoeganda, 2006b;Lisnawita et al, 2012;Nugrahana et al, 2017;Syafi'i et al, 2018). At 100 J2/100 g soil, PCN can cause 11% potato yield loss in Western Europe (Hadisoeganda, 2006a).…”
Section: Nematode Infestation and Crop Yield Lossmentioning
confidence: 99%
“…The presence of PPNs on potato plants in Indonesia has been documented in some prior studies; these studies indicated that major potato-growing regions across the country, including Wonosobo, Batu City, and several locations in West Java, were all likely to be infected by nematodes (Aprilyani et al 2015;Syafii et al 2018). However, in Indonesia, the diversity of PPNs that infect potato plants and their diversity at various altitudes still needs further study.…”
Section: Introductionmentioning
confidence: 95%